Energy Management Strategy Based on Model Predictive Control-Differential Evolution for Hybrid Energy Storage System in Electric Vehicles - Yaohua Tang; Junchao Xie; Yongpeng Shen; Songnan Sun; Yuanfeng Li (IET Electrical Systems in Transportation)
This paper addresses challenges related to the short service life and low efficiency of hybrid energy storage systems. A semiactive hybrid energy storage system with an ultracapacitor and a direct current (DC) bus directly connected in parallel is constructed first, and then related models are established for the lithium-ion battery, system loss, and DC bus. Based on the multiobjective evaluation function, a hybrid energy storage system Model Predictive Control-Differential Evolution (MPC-DE) energy management method is proposed. Experiments were conducted under China Light-Duty Vehicle Test Cycle-Passenger Car (CLTC-P) and Highway Fuel Economy Test (HWFET) driving cycles. The experimental results show that compared with other methods, this strategy can effectively reduce the loss of lithium-ion battery and ultracapacitor hybrid energy storage system and improve the system efficiency.